Gene pyramiding for bacterial blight resistance in rice variety Uma (Mo 16) - Tintumol Joseph (Department of Plant Breeding and Genetics, College of Horticulture, 2016)
Exploiting host-plant resistance through pyramiding of resistance genes have been recommended as the best approach to impart durable resistance to rice varieties in order to combat the bacterial blight (BB) disease caused by Xanthomonas oryzae pv.oryzae (Xoo). In lieu of this, F1s were produced by hybridizing the susceptible elite rice variety Uma with resistant donor parent Improved Samba Mahsuri (ISM) harbouring three R-genes xa5, xa13 and Xa21. BC1F1 individuals were generated by backcrossing the F1s using variety Uma as the recurrent parent. The present study aimed to identify the R-genes introgressed individuals in the BC1F1 population as well as to produce BC2F1s and BC1F2s of the identified R-genes introgressed BC1F1s. Foreground selection of the BC1F1 individuals was done using the R gene linked molecular markers. Restriction digestion of the PCR product of STS marker RG 556, linked to R gene xa5, with Dra1 restriction enzyme, resulted in production of alleles of size 128 bp, 514 bp, 587 bp, 624 bp, 650 bp and 836 bp in all the BC1F1 individuals as well as the parents indicating the presence of R gene xa5 in all the individuals studied. Amplification of DNA of the individuals with the functional marker xa5 SR further confirmed the presence of R gene xa5 in both the parents as well as in all the BC1F1s. Restriction digestion of the PCR product of STS marker RG 136, linked to R gene xa13, with Hinf1, produced alleles similar to that of the donor parent ISM in three BC1F1s namely, plant no. 8.3.2, plant no. 8.3.3 and plant no. 8.3.9, indicating the presence of R gene xa13 in these plants. The presence of gene xa13 in the identified BC1F1s was further affirmed by using the functional marker xa13 promoter. The analysis had resulted in the production of 560bp allele associated with the resistant allele of gene xa13 in homozygous state from donor parent ISM in the three BC1F1s mentioned above. Out of the 95 BC1F1 individuals scored with the STS marker pTA 248 linked to R gene Xa21, only BC1F1s plant no. 8.3.2, plant no. 8.3.3 and plant no. 8.3.9 were found to possess Xa 21. Results thus obtained revealed thatBC1F1plant no. 8.3.2, plant no. 8.3.3 and plant no. 8.3.9 were R gene pyramids (xa 5+xa 13+ Xa 21). Background profiling of the three R-genes introgressed BC1F1s using 22 rice microsatellite markers, revealed presence of the donor parent allele in the homozygous state. PCR analysis with the marker RM 307, however, revealed the presence of alleles from both the parents, ISM and Uma in the BC1F1 plant no. 8.3.2. This indicated that the plant was heterozygous at the marker locus and can be expected to segregate for the alleles at this locus in subsequent generations. Considering the segregation of the 22 markers the per cent recurrent parent genome recovery in the R-genes introgressed BC1F1s was estimated to be higher in BC1F1 plant no.8.3.2 but lower than the expected estimate of 75 per cent. This was also confirmed by graphical genotyping. The dendrogram thus generated out of the marker data, grouped the R-genes introgressed BC1F1s with ISM indicating that the three R-genes introgressed BC1F1s exhibited greater similarity with donor parent parent ISM at the genome level. Evaluation of BC1F1 individuals for morphological traits revealed presence of wide variability. The three R-genes introgressed BC1F1s were late in flowering compared to the recurrent parent Uma. Two of these genotypes i.e.,plant no. 8.3.2 (234 days) and plant no. 8.3.3 (228 days) flowered later than the donor parent. However, the three R-genes introgressed BC1F1s resembled the recurrent parent Uma with respect to grain and kernel characteristics. Backcrossing the three R-genes introgressed BC1F1s i.e., plant no. 8.3.2, plant no. 8.3.3 and plant no. 8.3.9 to the recurrent parent Uma resulted in 28 BC2F1s. Simultaneously, selfing of these individuals produced 850 BC1F2 seeds. Foreground and background profiling of these generations can ensure precise identification of genotypes that resembles the recurrent parent Uma possessing the resistance genes of interest with maximum recovery of recurrent parent genome.